Innovationen im Zuge der Digitalisierung des Personenverkehrs - Klaus Lütjens; Marius Radde; Gernot Liedtke; Sven Maertens; Thomas Standfuß; Benedikt Scheier; Kathrin Viergutz (Wirtschaftsdienst, 2018)
Die zunehmende Digitalisierung verändert das Angebot an Verkehrsdienstleistungen auf verschiedenen Ebenen. Die entsprechenden Innovationen sind teilweise inkrementell, teilweise auch radikal. So lässt sich beispielsweise das Fahrtenangebot eines Anbieters im öffentlichen Personennahverkehr vollkommen individualisieren und nach dem Mobilitätsbedarf der Nutzer ausrichten. – – The transport system is an important sector in economies, both in terms of its own share of gross national product and in its role as a presupplier, prime location and facilitator of private and occupational mobility. Like other industries, the transport system is subject to changes in technological trends, especially with regards to digitalisation. When analysing the forms and effects of digitalisation, one may be overwhelmed by the multitude of terms, such as: Industry 4.0, Physical Internet, Internet of Things, Radical Innovation, New Business Models and Digital Transformation. These terms are often interpreted in different ways because they have been specifi cally designed for agenda setting and thus for the enforcement of the individual interests of consultants, researchers and industries. And while transport has high hopes for digitalisation, it doesn't necessarily apply to all parameters of the transport system. There are several relevant issues to consider including the extent to which digitalisation affects the traffic supply and demand and whether this will lead to an increase or decrease in traffi c movements.
Keywords: L9; O3; R4; 330